Associations of extended work, higher workloads and emotional work demands with sleep disturbance among night-shift workers - Bo Min Jeon; Su Hyun Kim (BMC, 2022)
Abstract Background In-depth investigation of the factors that exacerbate sleep disturbance among night-shift workers is essential to develop a successful implementation strategy to improve sleep. Although some characteristics of work associated with sleep disturbances have been investigated, there are inconsistencies in the findings. This study aimed to assess the influence of working time and work characteristics on sleep disturbance among night-shift workers. Methods This study was a secondary data analysis of a nationally representative sample of data from the fifth Korean Working Condition Survey in 2017. A total of 1,790 wage workers aged between 19 and 64 years with night shift schedules were selected and analyzed. A multiple logistic regression analysis was conducted to analyze the influences of working time characteristics, including shift type, frequency of night shift, and extended work; as well as work characteristics, including physical work demands, workload, emotional work demands, social support, and communication, on sleep disturbance among night-shift workers. Results Of those analyzed, 8.4% of night-shift workers experienced sleep disturbances. Night-shift workers with extended work, higher workloads, and emotional work demands were more likely to experience sleep disturbances (OR = 1.53, 95% CI = 1.05 to 2.23; OR = 1.01, 95% CI = 1.01 to 1.03; OR = 1.03, 95% CI = 1.02 to 1.05; respectively). Conclusion Extended work, higher workload, and emotional work demands were significant factors for sleep disturbance among night-shift workers. These findings highlight the importance of adjusting work demands and mitigating extended work to reduce sleep disturbance in night-shift workers.